CONTROL-WAVE: Gesture Control Glove - Yogita Deepak Mane; Dr. Neeta Patil; Akshay Agrawal (ITEGAM-JETIA)
This Research work aims to address the challenges faced by teaching professionals in the Education as well as industry sector by developing an innovative wearable device known as Gesture control Glove named as control-wave equipped with advanced gesture recognition technology. Through a comprehensive understanding of the issues encountered by all the Teaching professionals, particularly regarding the navigation of digital content during lectures, the proposed research work seeks to create a comfortable, intuitive, and efficient tool that enhances their teaching experience.